Sociopragmatic Imperative Speech of ‘Amak-Amak’ on Cooking Activities in The Manujueh Days Tradition in Nagari Salayo - Ihsanul Fuadi Yusda; Ike Revita; Aslinda Aslinda (Puitika, 2022)
This study aims to determine the imperative sociopragmatics form on speech of ‘amak-amak’ during the cooking process for the ‘manujueh hari’ tradition in Nagari Salayo in March 2020. The method used in this study is descriptive qualitative method. The results of the analysis of this study reveal that there are 33 imperative sociopragmatic forms of data used as imperative sociopragmatics analysis material. 6 advertisements in the form of imperative sociopragmatic ordinary, 11 advertisements in the form of imperative sociopragmatic licensing, 7 advertisements in the form of imperative sociopragmatic invitations, 9 advertisements in the form of imperative sociopragmatic orders. Based on the results of this analysis, it can be concluded that the form of sociopragmatics that often arises is licensing sociopragmatics.